Implementasi Sistem Informasi Akuntansi Berbasis Web pada Instansi Militer di Kolatmar Puslatmar-8 Teluk Ratai - Yosi Khoirunnisa; Heni Sulistiani (LPPM STIKI MALANG, 2024)
This research aims to design a web-based Accounting Information System (SIA) to optimize cash book management in Kolatmar Puslatmar-8 Teluk Ratai. The method used is Rapid Application Development (RAD) which consists of four stages: needs planning, user design, construction, and cutover. The system was developed using PHP as a programming language and MySQL as a database management system. Research results show that the web-based SIA designed has features such as transaction data management, categorization, financial reporting, and debt-debt management. The system uses a three-tiered access structure consisting of the Treasury Staff, Administrator, and Chief. Black box testing shows that the system has met the basic needs of Kolatmar Puslatmar-8 Teluk Ratai in cash book management. Implementation of this system has the potential to improve efficiency and accuracy in the financial management of institutions. However, further development and testing are needed to ensure the reliability, security, and scalability of the system in the long term.